Multivalued Coincidence Point Results in Partially Ordered Metric Spaces: Binayak S. Choudhury, Nikhilesh Metiya - Team, Support (Thai Journal of Mathematics, 2018)
Kannan type mappings hold an important position in metric fixed point theory. In this paper we define generalized multivalued Kannan type mappings and establish some coincidence point theorems for an arbitrary family of multivalued mappings with another single valued self mapping in partially ordered metric spaces. The corresponding single valued cases are discussed. One illustrative example is also given. The method of proofs here is a blending of order theoretic and analytic methodologies.